(untitled) - Bui, Thi Nga (Vietnam, 1998)
The fungicide fluazinam, the insecticide lambda-cyhalothrin, and the herbicides asulam and metamitron were applied to indoor freshwater microcosms (water volume approximately 0.6 m3). The treatment regime was based on a realistic application scenario in tulip cultivation. Concentrations of each pesticide were equal to 0%, 0.2%, 0.5%, 2%, and 5% spray drift emission of label-recommended rates. Contribution of compounds to the toxicity of the pesticide package was established by expressing their concentrations as fractions of toxic units. The fate of the compounds in the water, and responses of phytoplankton, zooplankton, periphyton, macroinvertebrates, macrophytes, decomposition, and water quality were followed for 13 weeks. The half-lives of lambda-cyhalothrin, metamitron, and fluazinam were 1 to 2 d; that of asulam was >30 d. No consistent effects could be demonstrated for the 0.2% treatment regime that was therefore considered the no-observed-effect concentrationcommunity (NOEC). The macroinvertebrate populations of Gammarus pulex, Asellus aquaticus, and Proasellus meridianus were the most sensitive end points, followed by species of copepods and cladocerans. Responses mainly were due to lambda-cyhalothrin. The 0.5% treatment regime resulted in short-term effects. Pronounced effects were observed at the 2% and 5% treatment levels. At the end of the experiment, the macrophyte biomass that consisted of Elodea nuttallii, showed a decline at the two highest treatment levels, asulam being the causal factor (NOEC: 0.5% treatment level). Primary production was reduced at the 5% treatment level only. In our experiment, the first-tier risk assessment procedure for individual compounds was adequate for protecting sensitive populations exposed to realistic combinations of pesticides. Spray drift reduction measures seem to be efficient in protecting aquatic ecosystems in agricultural areas.
Keywords: Aquatic ecology,Water,Ecological risk assessment,Đánh giá rủi ro sinh thái,Nước,Thủy sản sinh thái; Pollution,Ô nhiễm